2015
DOI: 10.1007/s13277-015-4542-4
|View full text |Cite
|
Sign up to set email alerts
|

SphK1 promotes tumor cell migration and invasion in colorectal cancer

Abstract: Colorectal cancer (CRC) is one of the most common cancers worldwide. Sphingosine kinase 1 (SphK1), which phosphorylates sphingosine to sphingosine-1-phosphate (S1P), is overexpressed in various types of cancers and may act as an oncogene in tumorigenesis. However, little is known about the role of SphK1 in CRC patients. We studied the expression of SphK1 in 85 cases of CRC tissues by immunohistochemistry, qRT-PCR, and western blot. We also evaluated the effect of SphK1 on cell proliferation and invasion by MTT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 23 publications
3
30
0
1
Order By: Relevance
“…A cancer therapeutic directed against S1P would, ideally, shift the S1P rheostat toward reduced S1P production (1). This concept is supported by preclinical studies in multiple cancer types that demonstrate increased tumor growth when S1P is elevated either due to increased synthesis as a result of SPHK1/2 upregulation (7,8) or due to decreased S1P degradation as a result of SGPL1/2 inhibition (53). In the current study, we demonstrate that metformin reduces S1P levels by downregulating SPHK1.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…A cancer therapeutic directed against S1P would, ideally, shift the S1P rheostat toward reduced S1P production (1). This concept is supported by preclinical studies in multiple cancer types that demonstrate increased tumor growth when S1P is elevated either due to increased synthesis as a result of SPHK1/2 upregulation (7,8) or due to decreased S1P degradation as a result of SGPL1/2 inhibition (53). In the current study, we demonstrate that metformin reduces S1P levels by downregulating SPHK1.…”
Section: Discussionsupporting
confidence: 72%
“…Sphingosine kinases (SPHK), including SPHK1, catalyze the formation of S1P from sphingosine and are pivotal regulators of the balance between ceramides, sphingosine and S1P. Increased expression of SPHK1 promotes tumor growth and metastasis in breast, colorectal, and lung cancers (1, 3,7,8), and the role of the S1P pathway is becoming increasingly relevant in ovarian cancer (9,10). Two older studies reported higher S1P levels in the serum and ascites in ovarian cancer patients compared with controls (11,12), and a more recent study showed that SPHK1 is highly expressed in tumor stroma of high-grade serous ovarian cancer (13).…”
Section: Introductionmentioning
confidence: 99%
“…SK1 expression is elevated in the majority of human CRC specimen (78-89%). 64,65 A similar increase in SK1 expression was detected in the AOM carcinogenesis model. 64 Elevated expression of SK1 also increases the susceptibility to colitis-associated cancer.…”
Section: Sphingosine Kinasessupporting
confidence: 66%
“…MiR-125b in bladder cancer upregulates Trop-2, SphK1, E2F3, SIRT7, MALAT1, and MMP13 to promote cancer tumorigenesis and metastasis. 67,68 In HCC, miR-125b regulates many genes involved in various mechanisms. The downregulation of miR-125b causes the overexpression of EIF5A2, which is known to be associated with proliferation and poor prognosis in patients with CRC and NSCLC.…”
Section: Downregulation Of Mir-125b In Cancermentioning
confidence: 99%
“…13,19,22,62 As tumor suppressors, miR-125b can promote the PI3K/Akt, TGFβ, and ERBB2/Her2 signaling. 67,68,72,78…”
Section: Mir-125b In Cancer Diagnosis and Prognosismentioning
confidence: 99%